2011
DOI: 10.2165/11587870-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Hyperhidrosis

Abstract: Hyperhidrosis is a disorder of excessive sweating beyond what is expected for thermoregulatory needs and environmental conditions. Primary hyperhidrosis has an estimated prevalence of nearly 3% and is associated with significant medical and psychosocial consequences. Most cases of hyperhidrosis involve areas of high eccrine density, particularly the axillae, palms, and soles, and less often the craniofacial area. Multiple therapies are available for the treatment of hyperhidrosis. Options include topical medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 97 publications
1
87
0
10
Order By: Relevance
“…For this, a dermatological workup is indicated in all patients seeking help, including clinical and laboratory investigations as well as psychosocial assessment [7]. A variety of treatment options is available and can be applied according to the trigger factors and causes of hyperhidrosis [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…For this, a dermatological workup is indicated in all patients seeking help, including clinical and laboratory investigations as well as psychosocial assessment [7]. A variety of treatment options is available and can be applied according to the trigger factors and causes of hyperhidrosis [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…11,12 A review of oral anticholinergic therapy for hyperhidrosis indicated that 40% of subjects in clinical studies withdraw from the treatment due to AEs. 9 Consequently, developing topical anticholinergic drugs is an ideal approach to treat hyperhidrosis as sweat glands are surrounded with cholinergic sympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Oral oxybutynin is an important option in managing this condition, especially in patients with multifocal hyperhidrosis [1], and has improved HR-QOL-related measures in uncontrolled studies [5,6] ( Table 1). Oral glycopyrrolate (1-2 mg up to three times daily) is also used in the treatment of craniofacial hyperhidrosis [7]; it has shown some promising results in retrospective studies in patients with hyperhidrosis affecting a variety of body sites (response rate of &67 [8] and 79 % [9]), but studies in patients with craniofacial hyperhidrosis are lacking. Topical glycopyrrolate reduced sweat production in a small study [10] ( Table 1); further studies are needed to determine its optimal application regimen and long-term effectiveness [1].…”
Section: Apply Anticholinergics Topically or Take Orallymentioning
confidence: 99%
“…Fig. 1 Management of primary focal craniofacial hyperhidrosis, as suggested by Nicholas et al [1] Evidence lacking for other options Other pharmacological agents, including topical 20 % aluminium chloride hexahydrate solution, oral clonidine and oral propranolol, have been be used to treat craniofacial hyperhidrosis in clinical practice [1,7]; however, the systematic review by Nicolas et al did not identify any experimental or observational studies supporting their use in this specific indication [1].…”
Section: Inject Botulinum Toxin Amentioning
confidence: 99%